Role of Metal Oxide Nanomaterials on Thermal Stability of 1, 3, 6‐Trinitrocarbazole. Issue 5 (28th July 2016) - Pourmortazavi, Seied Mahdi; Rahimi‐Nasrabadi, Mehdi; Rai, Hossein; Besharati‐Seidani, Abbas; Javidan, Abdollah
Abstract: The thermal behaviour of 1, 3, 6‐trinitrocarbazole (TENT) in the form of pure and nanocomposite explosives was examined by differential scanning calorimetry (DSC) and thermogravimetry (TG). Thermoanalytical data revealed that thermal decomposition of pure TENT is significantly different from the investigated nanocomposites. The results confirmed that pure TENT decomposed completely in a single stage in the temperature range 400–450 °C. Though, addition of the nanoparticles to the TENT powder leads to higher thermal stability in comparison with the pure TENT. Decomposition kinetics of the pure TENT and the nanocomposites were studied by non‐isothermal DSC at diverse heating rates. The resulted thermokinetic and thermodynamic parameters for the thermal decomposition of pure TENT were compared with the nanocomposites. Abstract :